Argentina : Technical Assistance Report-Staff Technical Note on Public Debt Sustainability. (IMF Staff Country Reports; Country Report, 2020)
This Technical Assistance report on Argentina sets out IMF staff's views on a feasible macroeconomic framework that could underpin a debt restructuring operation that would restore debt sustainability with high probability. Given that the authorities are in the process of elaborating the precise content of their policy agenda, the feasible macroeconomic framework is anchored around the authorities' broad policy announcements and predicated on the IMF staff's view that a set of policies could be fully developed and implemented to render the macroeconomic framework achievable. However, there are important downside risks to the feasible macroeconomic framework, especially if the adverse global and domestic economic effects of the fast-moving COVID-19 pandemic are larger and more prolonged than assumed in this note. Economic conditions are rapidly worsening, and financial conditions are characterized by very high volatility. This greatly increases the uncertainty about the macroeconomic framework, with potential implications for the IMF staff's assessment of debt sustainability.